Most eastern boundary upwelling regions represent thermal refugia in the age of climate change - García-Reyes, Marisol; Koval, Gammon; Sydeman, William J.; Palacios, Daniel; Bedriñana-Romano, Luis; DeForest, Kelly; Montenegro Silva, Carlos; Sepúlveda, Maritza; Hines, Ellen (Frontiers in Marine Science, 2023)
Eastern Boundary Upwelling Systems (EBUS) are regions where wind-driven coastal upwelling brings deep cold, nutrient-rich water to the surface and may be characterized by a coastal ‘footprint’ of sea surface temperature (SST) cooler than their surroundings. Previous studies have shown that EBUS coastal temperatures are responding differently to global ocean warming, warming slowly or not at all. However, the spatial dynamics of coastal upwelling footprints have yet to be investigated. In this paper, we use 20 years of high-resolution SST data derived from satellites (MUR SST) to test the null hypothesis that the extent of coastal upwelling footprints have remained stable over the period 2002–2022, consistent with the idea that these regions are thermal refugia. We investigate linear trends at different time scales, finding that the Humboldt and Iberian/Canary EBUS show no contraction of this footprint on annual or seasonal scales. The Benguela EBUS shows no change in its central and poleward subregions, but it exhibits contraction of the footprint in the equatorward subregion in the austral winter and spring. The California EBUS behaves differently: on the annual scale only the equatorward subregion shows contraction of the SST footprint, while on the seasonal scale, the entire EBUS show contraction during the fall or summer/fall. Summarizing the last two decades, most coastal habitats of EBUS (>80% of the areas tested) are remaining cool and may be acting as regional refugia from global warming, but this is true for some regions only during certain seasons. However, the declines in areal extent of upwelling in subregions of the California and Benguela EBUS indicate potential consequences for marine life and may help to explain changes in abundance, productivity, and redistributions of populations in these regions.